Impact of long-term chemotherapy (CTx) on outcomes in pancreatic ductal adenocarcinoma (PDAC): A real-world UK multi-centre study - Bridgewater, John; Lynch, Joanna; Sandhu, Simran Kaur; Hochhauser, Daniel; Shiu, Kai-Keen; Smyth, Elizabeth Catherine; Khan, Khurum Hayat (Journal of clinical oncology, 2025)
687Background: PDAC is associated with poor outcomes with limited treatment options. Here, we present a multi-institutional review evaluating outcomes following short and long-term CTx with or without treatment breaks in PDAC patients (pts). Methods: All consecutive PDAC pts receiving > 3 CTx cycles between 2019 - 2023 at University College London Hospitals and Oxford University Hospitals were included. Treatment response, survival outcomes and predictors of clinical benefit were evaluated. Wilcoxon test, Kaplan-Meier and multivariate Cox regression models were performed. Results: Of the 213 screened pts, 127 eligible subjects met the study criteria. 1st, 2nd and 3rd line CTx were received by 127, 40 and 2 pts, respectively. 21 pts had resectable disease (9 remained relapse-free after adjuvant CTx and 8 pts alive at post 2 years follow-up surveillance). 106 pts had unresectable or metastatic disease and were selected for final analyses (12% borderline resectable (BR), 19% locally advanced (LA), 9% localised disease who developed metastases and 60% de novo metastatic pts). 7 pts (7%) pts underwent genetic profiling on pt request or previous clinical trial screening; KRAS aberrations (N = 4), actionable PLAB2 / BRCA2 mutations (N = 2). BR and LA pts (N = 33) achieved a median PFS1 (Progression Free Survival while on 1st line CTx) of 8.28 (95% Confidence Interval (CI), 5.49 - 15.11) and Overall Survival (OS) of 15.15 (95% CI, 9.46 - 26.41) months (mos). De novo metastatic pts (N = 64) attained a PFS1 of 6.64 (95% CI, 5.98 - 8.18) and OS of 9.30 (95% CI, 8.05 - 12.81) mos. Patient-specific factors in both cohorts comprising of age, gender, performance status, smoking history, co-morbidities were not associated with PFS1 and OS. Improved PFS was associated with ≥ 6 cycles of 1st line CTx (P = < 0.001), median duration of 1st CTx of ≥ 3.58 mos (P = < 0.001) and best response to 1st CTx (P = 0.007). A favourable OS was associated with > 1 line of CTx (P = < 0.001), ≥ 6 cycles of 1st line CTx (P = 0.009), median duration of 1st CTx of ≥ 3.58 mos (P = < 0.001) and best response to 1st CTx (P = 0.002). Subjects receiving ≥ 6 cycles of 1st CTx were younger than pts tolerating fewer cycles (median age 62.41 vs 72.25 years) (P = 0.04). In the localised disease group, improved PFS was associated with ≥ 6 cycles of 1st line CTx (P = 0.003), median duration of 1st CTx of ≥ 2.99 mos (P = 0.008) and local treatment after commencing 1st line CTx (P = < 0.001). These three factors were also associated with OS; P = 0.02, P = 0.02 and P = < 0.001, respectively. Median number and duration of 1st line CTx interruptions were not associated with PFS1 or OS in both cohorts. Conclusions: Despite challenges associated with long-term CTx, survival outcomes may be better in pts receiving CTx for longer periods and multiple treatment lines. Genetic profiling currently offers limited value but in carefully selected pts, localised treatment options may be associated with improved survival outcomes.